Physics essentials for dummies - Holzner, Steven; Wohns, Daniel (Hoboken, NJ Wiley Publishing, Inc., 2010)
From the Publisher: For students who just need to know the vital concepts of physics, whether as a refresher, for exam prep, or as a reference, Physics Essentials For Dummies is a must-have guide. Free of ramp-up and ancillary material, Physics Essentials For Dummies contains content focused on key topics only. It provides discrete explanations of critical concepts taught in an introductory physics course, from force and motion to momentum and kinetics. This guide is also a perfect reference for parents who need to review critical physics concepts as they help high school students with homework assignments, as well as for adult learners headed back to the classroom who just need a refresher of the core conce.
Introduction -- About this book -- Conventions used in this book -- Foolish assumptions -- Icons Used in this book -- Where to go from here -- Chapter 1: Viewing The World Through The Lens Of Physics -- Figuring out what physics is about -- Paying attention to objects in motion -- Getting energized -- Moving as fast as you can: special relativity -- Measuring your world -- Keeping physical units straight -- Converting between units of measurement -- Nixing some zeros with scientific notation -- Knowing which digits are significant -- Chapter 2: Taking Vectors Step By Step -- Getting a grip on vectors -- Looking for direction and magnitude -- Adding vectors -- Subtracting vectors -- Waxing numerical on vectors -- Working with vector components -- Using magnitudes and angles to find vector components -- Using vector components to find magnitudes and angles -- Chapter 3: Going the distance with speed and acceleration -- From here to there: dissecting displacement -- Examining axes -- Measuring speed -- Fast track to understanding speed and velocity -- How fast am I right now? instantaneous speed -- Staying steady: uniform speed -- Changing your speed: nonuniform motion -- Doing some calculations: average speed -- Contrasting average speed and instantaneous speed -- Speeding up (or slowing down): acceleration -- Defining our terms -- Recognizing positive and negative acceleration -- Looking at average and instantaneous acceleration -- Accounting for uniform and nonuniform acceleration -- Bringing acceleration, time, and displacement together -- Locating not-so-distant relations -- Equating more speedy scenarios -- Putting speed, acceleration, and displacement together -- Chapter 4: Studying Circular Motions -- Understanding uniform circular motion -- Creating centripetal acceleration -- Seeing how centripetal acceleration controls velocity -- Calculating centripetal acceleration -- Finding angular equivalents for linear equations -- Chapter 5: Push-Ups and Pull-Ups: Exercises in Force -- Reckoning with force -- Objects at rest and in motion: Newton's first law -- Calculating net force: Newton's second law -- Gathering net forces -- Just relax: dealing with tension -- Balancing act: finding equilibrium -- Equal and opposite reactions: Newton's third Law -- Chapter 6: Falling Slowly: Gravity And Friction -- Dropping the apple: Newton's law of gravitation -- Down to Earth: dealing with gravity -- Leaning vertically with inclined planes -- Facing friction -- Figuring out the normal force -- Finding the coefficient of friction -- Bringing static and kinetic friction into the mix -- Getting moving with static friction -- Staying in motion with kinetic friction -- Dealing with uphill friction -- Calculating the component weight -- Determining the force of friction -- Chapter 7: Putting Physics To Work -- Wrapping your mind around work -- Pushing your weight -- Taking a drag -- Working backward: negative work -- Working up a sweat: kinetic energy -- Breaking down the kinetic energy equation -- Using the kinetic energy equation -- Calculating kinetic energy by using net force -- Saving up: potential energy -- Working against gravity -- Converting potential energy into kinetic energy -- Pitting conservative against nonconservative forces -- No work required: the conservation of mechanical energy -- Powerful idea: the rate of doing work -- Chapter 8: Moving Objects With Impulse And Momentum -- Feeling a sudden urge to do physics: impulse -- Mastering momentum -- Connecting impulse and momentum -- Taking impulse and momentum to the pool hall -- Getting impulsive in the rain -- Watching objects go bonk: the conservation of momentum -- Measuring firing velocity -- Examining elastic and inelastic collisions -- Flying apart: elastic collisions -- Sticking together: inelastic collisions -- Colliding along a line -- Colliding in two dimensions -- Chapter 9: Navigating The Twists And Turns of Angular Kinetics -- Changing gears (and equations) from linear to rotational motion -- Tackling tangential motion -- Calculating tangential speed -- Figuring out tangential acceleration -- Looking at centripetal acceleration -- Applying vectors to rotation -- Analyzing angular velocity -- Working out angular acceleration -- Doing the twist with torque -- Walking through the torque equation -- Mastering lever arms -- Identifying the torque generated -- Realizing that torque is a vector -- No spin, just the unbiased truth: rotational equilibrium -- Chapter 10 Taking A Spin With Rotational Dynamics -- Converting Newton's second law into angular motion -- Moving from tangential to angular acceleration -- Bringing the moment of inertia into play -- Finding moments of inertia for standard shapes -- Doing rotational work and producing kinetic energy -- Making the transition to rotational work -- Solving for rotational kinetic energy -- Going round and round with angular momentum -- Chapter 11: There And Back Again: Simple Harmonic Motion -- Homing in on Hooke's law -- Staying within the elastic limit -- Exerting a restoring force -- Deja vu all over again: simple harmonic motion -- Browsing the basics of simple harmonic motion -- Exploring some complexities of simple harmonic motion -- Breaking down the sine wave -- Getting periodic -- Studying the velocity -- Including the acceleration -- Finding angular frequencies of masses on springs -- Examining energy in simple harmonic motion -- Going for a swing with pendulums -- Chapter 12 Ten Marvels Of Relativity -- Nature doesn't play favorites -- Speed of light is constant -- Time contracts at high speeds -- Space travel slows down aging -- Length shortens at high speeds -- Matter and energy are equivalent: E = mc2 -- Matter + antimatter equals boom -- Sun Is losing mass -- You can't surpass the speed of light -- Newton was right -- Index.
Includes index.
Keywords: Physics; Force and energy